Effect of infill pattern of polylactide acid (PLA) 3D-printed integral sandwich panels under ballistic impact loading - Ma, Quanjin; Mohd Ruzaimi, Mat Rejab; Song, Yiheng; Zhang, Xin; Hanon, Muammel M.; M. H., Abdullah; Kumar, A. Praveen (Elsevier Ltd, 2024)
This paper investigates the effect of the infill pattern of polylactide acid (PLA) 3D-printed sandwich panels under ballistic impact loading. Fused deposition modeling (FDM) technique is used to manufacture the PLA 3D-printed integral sandwich panels with four infill patterns: cubic, grid, gyroid, and honeycomb. The ballistic data acquisition system is collected the experimental results with three impact velocities: 109.65, 173.97, and 209.48 m/s. It was revealed that the 3D-printed sandwich panel with cubic infill pattern reached the highest maximum impact load than the other three infill patterns. Moreover, it was highlighted that the sandwich panel with cubic and gyroid infill patterns absorbed 1.41 and 1.15 J and provided better impact resistance characteristics. It is highlighted that the infill pattern plays a vital role in the impact resistance of 3D-printed sandwich structures. Furthermore, it is recommended the three-dimensional (3D) infill pattern, e.g., cubic, gyroid, 3D honeycomb, can provide better impact performance than the two-dimensional (2D) infill pattern.